2006
DOI: 10.1007/s10706-005-1881-8
|View full text |Cite
|
Sign up to set email alerts
|

Water infiltration characteristics of unsaturated soil slope and its effect on suction and stability

Abstract: Rainfall has been considered the cause of the majority of slope failures and landslides that happened in regions experiencing high seasonal rainfalls. The mechanism of the failures was mainly due to the lost of matric suction of soils by rainwater. This paper presents the results of a laboratory model study on the effect of slope angle and surface cover on water infiltration into soil and soil matric suction. A field infiltration test is carried out for comparison. A parametric study is also done to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 2 publications
1
40
0
8
Order By: Relevance
“…Huat et al 2005Huat et al , 2006Rahardjo et al 2014;Leung et al 2015bLeung et al , 2015c have shown that actively growing plants could reduce infiltration rate and saturated permeability of the soil. They demonstrated grass roots tended to increase the air-entry suction and the size of hysteresis loop of SWRC.…”
Section: Introductionmentioning
confidence: 99%
“…Huat et al 2005Huat et al , 2006Rahardjo et al 2014;Leung et al 2015bLeung et al , 2015c have shown that actively growing plants could reduce infiltration rate and saturated permeability of the soil. They demonstrated grass roots tended to increase the air-entry suction and the size of hysteresis loop of SWRC.…”
Section: Introductionmentioning
confidence: 99%
“…This concept explains that above the ground water level, the value of pore water pressure is not positive, but negative. The reason behind the negative value is due to the existence of matric suction where cohesion-adhesion reaction fills in between the soil particle because the void is filled with both air and water at the same time [3,[6][7].…”
Section: Unsaturated Soilmentioning
confidence: 99%
“…7, it is shown that the largest FS reduction for each rainfall pattern is achieved at 30 o angle, followed by 60 o , and the least is 45 o . The behaviour that is shown on the three figures are likely because the steeper the slope, the less water will be infiltrated and the rest will turn into runoff [6,15]. o slope model (see Fig.3.).…”
Section: The Effect Of Different Slope Angles To Fs For Different Raimentioning
confidence: 99%
“…Although numerous field investigations (Blatz et al, 2004;Cui et al, 2005Cui et al, , 2010Gasmo et al, 1999;Kim and Lee, 2010;Li et al, 2005;Li et al, 2011;Lim et al, 1996;Ng et al, 2003;Rahardjo et al, 2005;Tsaparas et al, 2003;Tu et al, 2009;Zhan et al, 2007;Zhang et al, 2000) and laboratory model tests (Huang et al, 2008;Huat et al, 2006;Li et al, 2009b;Moriwaki et al, 2004;Take et al, 2004;Tohari et al, 2007) have been conducted on soil moisture responses to rainfall, comparisons of measured and calculated pore water pressure profiles (Trandafir et al, 2008) and changes in pore water pressure with time (Alonso et al, 2003;Huat et al, 2006;Lan et al, 2003;Sako et al, 2006) are still limited. It is very difficult to find a unique set of soil hydraulic parameters that could match all transient pore water pressure responses (Trandafir et al, 2008).…”
Section: Analytical and Numerical Solutionsmentioning
confidence: 99%
“…The extended Mohr-Coulomb failure criterion (Fredlund et al, 1978) is usually adopted. Stability charts for slope stability analysis under rainfall conditions based on the finite-element seepage analyses and limit equilibrium stability analyses were developed by Huat et al (2006). These stability charts provide geotechnical engineers with a tool for rapid assessment of the safety factor in response to a rainfall event.…”
Section: Geotechnical Engineering Volume 164 Issue Ge5mentioning
confidence: 99%